A Sensitive Immunochemical Assay for Measuring the Concentration of the Activated Protein C-protein C Inhibitor Complex in Plasma: - Strandberg, Karin; Kjellberg, Margareta; Knebel, Richard; Lilja, Hans; Stenflo, Johan (Thrombosis and Haemostasis, 2001)
Activated protein C (APC) is a serine proteinase that regulates blood coagulation. In plasma it is inhibited mainly by the protein C inhibitor (PCI). The plasma concentrations of APC-PCI complex is increased in hypercoagulative states such as deep venous thrombosis. Formation of the APC-PCI complex induces a drastic conformational change in PCI that exposes new epitopes (neoepitopes) on the molecule. We have devised a simple immunofluorometric sandwich assay for measurements of the concentrations of APC-PCI complex, employing as the catcher, a monoclonal antibody that has a high affinity (KD ≈ 4 × 10-11M) for a complexation-specific neoepitope that is expressed on PCI. A monoclonal antibody against protein C is employed as the tracer. The method gives a linear dose-response curve (0.06-50 πg/l), has a low detection limit (0.06 πg/l) and no crossreactivity with native PCI at physiologic plasma concentrations. We have now determined the concentration of the APC-PCI complex in healthy individuals.
Keywords: APC-PCI complex; immunochemical assay; hypercoagulability